Communication perspectives on popular culture - Herrmann, Andrew F., 1966-; Herbig, Art, 1977- (Communication perspectives in popular culture., 2016)
Communication Perspectives on Popular Culture contains all new writings from many important established scholars as well as brilliant young scholars in the communication field. Contributors explore new and emerging ways to approach popular culture - from case studies to emerging theories - as they examine how popular culture, media, and communication influence our everyday lives.